PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN JIGSAW PADA MATA PELAJARAN IPA KELAS IV MIS AL-BIDAYAH MUNASELI KABUPATEN ALOR TAHUN PELAJARAN 2024/2025 - rahman syafrudin; Jusriadi; Mutia Ake Prasong; Mukmin Amsidi (STKIP Muhammadiyah Kalabahi, 2026)
study aims to improve student learning outcomes through the application of the Jigsaw learning model in Natural Sciences (IPA) subjects for grade IV at MIS Al-Bidayah Munaseli. The background of this study is the low learning outcomes of students in science subjects caused by low interest and active participation of students during the learning process. The Jigsaw learning model was chosen because it is able to increase student involvement actively in group learning activities and encourage cooperation between students. This study uses a Classroom Action Research (CAR) approach which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were grade IV students of MI Al-Bidayah Munaseli in the 2024/2025 academic year totaling 19 students. Data were collected through observation, learning outcome tests, and documentation. The results of the study indicate that the application of the Jigsaw learning model can improve student learning outcomes. This is evidenced by the increase in the average value of students from cycle I by 67.5% and increased after the implementation of cycle II with an average value of 83.75%, as well as the increase in the number of students who achieved the Minimum Completion Criteria (KKM). In addition, student activity and participation in the learning process also showed a significant increase. Thus, it can be concluded that the Jigsaw learning model is effective in improving student learning outcomes in science subjects for grade IV at MI Al-Bidayah Munaseli.